Multi objective optimization model of CNC turning for minimizing processing time and carbon emission with real machining application - Cucuk Nur Rosyidi; Wahyu Widhiarso; Eko Pujiyanto (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The purpose of this research is to develop an optimization model of CNC turning process. The objective function of the model is to minimize processing time and carbon emission. We implemented the results of optimization with real machining application using a certain workpiece. Design/methodology/approach: The model in this research used multi objective optimization involving two objective functions, namely processing time which includes cutting time and auxiliary time and carbon emissions resulted from the electricity energy consumptions, cutting tool, cutting fluid or coolant, raw materials production, and chip removal. Findings: The results of multi objective optimization indicate that the model can be used to minimize the processing time and carbon emissions with the optimal cutting speed and feed rate are 193.7 m/minute and 0.405 mm/rev. The results of sensitivity analysis showed that the higher weights of processing time will decrease the cutting speed, while the higher carbon emissions weight will result in faster cutting speed. The weight has no effects on feed rate. Originality/value: This paper gives a real machining application to show the applicability of the optimization model.
Keywords: 650; multi objective optimization; process parameters; processing time; carbon emission; CNC turning; real machining application; Werkzeugmaschine; Durchlaufzeit; Treibhausgas-Emissionen; Multikriterielle Entscheidungsanalyse; Theorie